Agrochemicals increase risk of human schistosomiasis by supporting higher densities of intermediate hosts - Neal T. Halstead (Nature Portfolio, 2018)
Agrochemicals can affect the life cycle of human parasites in unexpected ways. Here, Halstead et al. show in mesocosm experiments that agrochemicals increase the density of snails hosting schistosome parasites, and modeling analysis suggests this could lead to increased risk of human schistosomiasis.